2012
DOI: 10.1089/gtmb.2011.0367
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Methylenetetrahydrofolate Reductase C677T Gene Polymorphisms in Algerian Infertile Men with Azoospermia or Severe Oligozoospermia

Abstract: The data suggest that the C677T MTHFR polymorphism is not a risk factor for idiopathic male subfertility in an Algerian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Previous epidemiological studies have suggested ethnicity as a factor, where only certain ethnic populations revealed an association between this SNP and male infertility (Gupta et al, 2011;Chellat et al, 2012;Naqvi et al, 2014;Gong et al, 2015). The men in this study, however, were not evaluated for ethnicity.…”
Section: Discussionmentioning
confidence: 80%
“…Previous epidemiological studies have suggested ethnicity as a factor, where only certain ethnic populations revealed an association between this SNP and male infertility (Gupta et al, 2011;Chellat et al, 2012;Naqvi et al, 2014;Gong et al, 2015). The men in this study, however, were not evaluated for ethnicity.…”
Section: Discussionmentioning
confidence: 80%
“…The impact of MTHFR gene SNPs on infertility risk has been studied in various ethnic groups [2], [13], [22][25], [27], [29], [37][43]. Most commonly studied MTHFR SNP, c.677C>T, has been established as a risk factor for male infertility in some populations [21–23, 37 and 39–41], but not in others [13], [24][25], [38], [42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Most commonly studied MTHFR SNP, c.677C>T, has been established as a risk factor for male infertility in some populations [21–23, 37 and 39–41], but not in others [13], [24][25], [38], [42][43]. c.677C>T has been suggested to infertility risk by two meta-analyses [3 and 21], but denied doing so by a recent meta-analysis [44].…”
Section: Discussionmentioning
confidence: 99%
“…Results of these studies are contradictory. The MTHFR c.677TT genotype has been reported to be a candidate genetic risk factor for infertility in male patients in the studies performed in Germany, South Korea, Chine, Brasil, Iran and North India (Bezold et al ., ; Park et al ., ; Zhou‐Cun et al ., ; Gava et al ., ; Safarinejad et al ., ; Naqvi et al ., ), whereas the other studies from Netherlands, Italy, Algeria, Morocco‐ North Africa and South India did not find an association (Ebisch et al ., ; Stuppia et al ., ; Chellat et al ., ; Eloualid et al ., ; Vani et al ., ). In a meta‐analysis focusing on the relationship between the MTHFR c.677C>T polymorphism and male infertility, Wu et al .…”
Section: Discussionmentioning
confidence: 98%